Using exercises to improve public health preparedness in Asia, the Middle East and Africa - Dausey, David J (BioMed Central, 2014)
BACKGROUND: Exercises are increasingly common tools used by the health sector and other sectors to evaluate their preparedness to respond to public health threats. Exercises provide an opportunity for multiple sectors to practice, test and evaluate their response to all types of public health emergencies. The information from these exercises can be used to refine and improve preparedness plans. There is a growing body of literature about the use of exercises among local, state and federal public health agencies in the United States. There is much less information about the use of exercises among public health agencies in other countries and the use of exercises that involve multiple countries. RESULTS: We developed and conducted 12 exercises (four sub-national, five national, three sub-regional) from August 2006 through December 2008. These 12 exercises included 558 participants (average 47) and 137 observers (average 11) from 14 countries. Participants consistently rated the overall quality of the exercises as very good or excellent. They rated the exercises lowest on their ability to identifying key gaps in performance. The vast majority of participants noted that they would use the information they gained at the exercise to improve their organization’s preparedness to respond to an influenza pandemic. Participants felt the exercises were particularly good at raising awareness and understanding about public health threats, assisting in evaluating plans and identifying priorities for improvement, and building relationships that strengthen preparedness and response across sectors and across countries. Participants left the exercises with specific ideas about the most important actions that they should engage in after the exercise such as improved planning coordination across sectors and countries and better training of health workers and response personnel. CONCLUSIONS: These experiences suggest that exercises can be a valuable, low-burden tool to improve emergency preparedness and response in countries around the world. They also demonstrate that countries can work together to develop and conduct successful exercises designed to improve regional preparedness to public health threats. The development of standardized evaluation methods for exercises may be an additional tool to help focus the actions to be taken as a result of the exercise and to improve future exercises. Exercises show great promise as tools to improve public health preparedness across sectors and countries.